Hope In The Midst Of Suffering A Buddhist Perspective - Gauthier, Tina Jitsujo (2016)
This paper is based on an interfaith panel I was on from June 17, 2016 at the Society for Pastoral Theology conference. Each of the five panel participants read papers written by the two keynote speakers.1 The first paper, written by Joretta L. Marshall, was called Collaborating Hope: Joining the In-Between Spaces, and the second, written by John Caputo, was called Hoping Against Hope: The Possibility of the Impossible. I enjoyed reading both papers, and found many correlations between the theologies written in these papers and my own understanding and practice of Buddhism. I was asked to give some reflections on "hope" from the Buddhist perspective. What I say here about hope is based on my own worldview, study, and practice. Know that my understanding may change, and my perspective does not necessarily reflect Buddhism as a whole, although it may reflect the whole.